2022
DOI: 10.1111/scd.12768
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of HLA‐B* 15:02 screening in trigeminal neuralgia and the gene screening policy among dentists in Southern Thailand

Abstract: Objectives To determine the factors associated with public hospital dentists’ awareness of HLA‐B*15:02 screening in trigeminal neuralgia (TN) and the national gene screening policy in Thailand. Methods Cross‐sectional study. A validated questionnaire was distributed to public hospital dentists with at least 1 year of practice in Southern Thailand (n = 760) to assess their knowledge of TN, carbamazepine (CBZ) use, awareness of HLA‐B*15:02 screening, and the gene screening policy. Results A total of 385 dentists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…RA was shown to be associated with HLA-DR4, which was also noted in the present case, but the arthritis did not worsen after vaccination. Previous studies have shown that Sjögren's syndrome was associated with HLA-DR3 (HLA-DRB1*03, HLA-DRB1*03:01) ( 27 ), and trigeminal neuropathy was associated with HLA-B15 (HLA-B15*02) ( 28 ), but these were absent in the present case. Conversely, IMNM was shown to be associated with not only HLA-DR8 (HLA-DRB1*08:03) ( 29 ) but also HLA-DR14 (HLA-DRB1*14:03) ( 30 ), which was present in our patient.…”
Section: Discussioncontrasting
confidence: 72%
“…RA was shown to be associated with HLA-DR4, which was also noted in the present case, but the arthritis did not worsen after vaccination. Previous studies have shown that Sjögren's syndrome was associated with HLA-DR3 (HLA-DRB1*03, HLA-DRB1*03:01) ( 27 ), and trigeminal neuropathy was associated with HLA-B15 (HLA-B15*02) ( 28 ), but these were absent in the present case. Conversely, IMNM was shown to be associated with not only HLA-DR8 (HLA-DRB1*08:03) ( 29 ) but also HLA-DR14 (HLA-DRB1*14:03) ( 30 ), which was present in our patient.…”
Section: Discussioncontrasting
confidence: 72%